The Association of Salivary Flow Rate and Sleep Quality among Head and Neck Cancer Survivors after Radiotherapy - Yen-Wen Shen; Wen-Chen Wang; Nan-Chin Lin; Valendriyani Ningrum; Tzong-Ming Shieh; Yin-Hwa Shih (BMC, 2024)
Abstract Background Head and neck cancer survivors suffer from xerostomia and sleep disturbances after radiotherapy, both of which affect their quality of life. This study aimed to explore the role of salivary flow in the oral health and sleep quality of head and neck cancer survivors. Methods We recruited 120 head and neck cancer survivors who were experiencing symptoms of dry mouth or sleep disturbances post-radiotherapy from a dental clinic. We gathered their socio-demographic and clinical data, measured their salivary flow rate, and recorded their dry mouth score using the summated xerostomia inventory. Additionally, a dentist collected the DMFT (Decayed, Missing, and Filled Teeth) index. The Pittsburgh Sleep Quality Index was employed to assess their sleep quality. Results In this study, xerostomia was observed in nearly 80% of the cancer survivors. The concurrent prevalence of sleep disturbance and xerostomia was at 55%. After five years post-radiotherapy, there was a significant improvement observed in both the quality of sleep (p = 0.03) and the stimulated salivary flow rate (p = 0.04). Additionally, these improvements were noted to have commenced from the third year onwards. A significant association was found between stimulated salivary flow and dry mouth scores with poor sleep quality (p <  0.05). Conclusions We recommend that dental professionals prioritize managing both dental and mental health issues equally for head and neck cancer survivors who have undergone radiotherapy within the past 3 years.